Cold plasma treatment of chickpeas: disinfestation potential, milling and baking quality of the flour - Bommina, Hemanth Sai Kiran (My University, 2025)
Chickpeas (Cicer arietinum L.) are an essential legume known for their high protein content, dietary fiber, and micronutrient composition. However, post-harvest losses due to insect infestations, particularly from Callosobruchus maculatus (F.), and Cowpea Weevil, pose significant storage and food security challenges. Traditional fumigation techniques rely on chemical treatments, contributing to environmental pollution and raising concerns about pesticide resistance and food safety. This research uses cold plasma technology, an innovative non-thermal pest control method for disinfesting C. maculatus different life stages. This research involved subjecting chickpea samples infested with C. maculatus eggs, larvae, pupae, and adults to varying cold plasma exposure conditions (15-25 kV for 5-15 min). The effectiveness of treatment was evaluated based on insect mortality rates and changes in physicochemical properties. Results demonstrated significant mortality rates, with 100% larval mortality achieved at 25 kV for 10 min and complete egg eradication at 20 kV for 15 min. Further, cold plasma treatment preserved the physical and nutritional properties of chickpeas, ensuring no adverse effects on bulk density, true density, moisture content, or kernel weight. Beyond disinfestation, this research also examined the potential of cold plasma-treated chickpea flour in food formulations, particularly in cookie production. Cookies made with treated chickpea flour were assessed for physical properties, texture, and sensory attributes. The findings confirmed that cold plasma treatment maintains the overall quality of the final product. This research showcases cold plasma as a sustainable alternative to chemical fumigation, effectively reducingpost-harvest losses from C. maculatus. Its findings advance food safety, grain storage, and non-thermal processing and play a key role in sustainable agriculture and food security.
Keywords: Cold plasma; Voltage; Time; Callosobruchus maculatus; Cookies